PSIKOEDUKASI UNTUK MENGURANGI STIGMA DIRI PADA PENDERITA GANGGUAN JIWA : SYSTEMATIC REVIEW - Safra Ria Kurniati; Mawar Eka Putri; Hotmaria Julia Dolok Saribu (Fakultas Keperawatan, Universitas Riau, 2023)
This study aimed to review the scientific evidence regarding psychoeducation as an intervention to help reduce self-stigma. Based on the literature research using the PRISMA flow diagram from three databases such as Science Direct, ProQuest, and PUBMED, 3903 articles from 2017 to 2022 were found and screened. The criteria for inclusion were articles that focus on severe mental illness , published in English, and original research with quantitative design. In the final process, 7 articles that met inclusion criteria were analyzed using the CASP tool. The result showed that psychoeducation is an effective intervention to reduce self-stigma. The measured values including stigma, empowerment, and perception of discrimination. Psychoeducation focused on reducing self-stigma by correcting inaccurate ideas about mental disorders, and the relationship between mental disorders and criminal activity or violence. Research evaluating psychoeducation on the self-stigma of the mentally ill patient is urgently needed to improve treatment, nursing care plans, and preventive measures for relapse.